Retrieval of Bamboo forests in Madhya Pradesh - Prasad, Ram; Chadhar, S. K. (Indian Forester, 1988)
With the increase in various developmental activities the demand for bamboo has been increased tremendously. To save the shrinking bamboo forests and to increase the yield of bamboos the necessary measures have been suggested and discussed.